Saving energy at university campus via intervention to reduce elevator usage – a case study from Germany - Gölitzer, Friederike; Barbir, Jelena; Eustachio, Joao Henrique Paulino Pires (Frontiers in Sustainability, 2023)
Recently, the need for energy saving has become a challenge for German society. Rising prices of energy, and urgent need to mitigate and adapt to climate change, made it necessary to reflect and change behaviours on a population level. Simultaneously, the population faces increased sedentary lifestyle and health system promotes benefits of daily movement and sports. By using stairs, instead of taking the elevator, could be part of the solution for both problems. This applies for buildings, such as universities, which usually have hundreds of students and staff circulating daily. In this sense, this study aims to analyse how an intervention to increase stair usage, by involving motivational stickers and posters, could impact the behaviour of students and staff. To achieve its goal, a field study and a questionnaire has been conducted at one German University. The results showed, after the intervention, that the elevator usage decreased by nearly 7%. According to the questionnaire nearly a fifth of all participants felt motivated by the stickers to choose the stairs over the elevator. While before the intervention male participants were 1.76 times more likely than females to take the stairs, the difference in stair usage after the intervention was not statistically significant anymore. Individual students and staff members were 1.44 times more likely to take the stairs than when grouped with others. This difference in stair usage individually or in a group increased from nearly 8% before the intervention to 17% after the intervention. Although short, the intervention showed to be successful and the results indicated that elevator interventions should be utilized in future contexts at a population level to spread the message that by reducing elevator usage, energy can be saved, and human fitness improved.